Effects of COVID-19 pandemic on mental health among frontline healthcare workers: A systematic review and meta-analysis - Tong, Jie; Zhang, Jie; Zhu, Na; Pei, Yu; Liu, Weiqing; Yu, Wei; Hu, Chengping; Sun, Xirong (Frontiers in Psychology, 2023)
Background: As some countries announced to remove COVID-19 border, it indicates that the COVID-19 may have entered its terminal stage. In this COVID-19 epidemic, the mental health of frontline healthcare workers (HCWs) experi-enced unprecedented challenges. However, the impact of the COVID-19 epidemic on mental health among frontline HCWs lacks a high-quality and long-term systematic review and me-ta-analysis. Methods: We conducted a systematic review and meta-analysis according to PRISMA guidelines. The system searches EMBASE, MEDLINE, PsycINFO, Cochrane Library, Sci-enceNet and ERIC. Analyze the mental health problems of frontline HCWs in different re-gions and periods, including insomnia, stress, anxiety and depression. This study was regis-tered in PROSPERO under the number CRD42021253821. Results: A total of 19 studies on the effects of COVID-19 epidemic on mental health among frontline HCWs were included in this study. The overall prevalence of insomnia was 42.9% (95% CI, 33.9% to 51.9%, I2 =99.0%) extracted from data from 14 cross-sectional studies (n=10 127), 1 cohort study (n=4804), and 1 randomized controlled trial (RCT) (n=482) in 10 countries. The overall prevalence of stress was 53.0% (95% CI, 41.1% to 64.9%, I2 = 78.3%) extracted from data from 9 cross-sectional studies (n = 5494) and 1 RCT study (n = 482) from 8 countries. The overall prevalence of anxiety and depression was 43.0% (95% CI, 33.8% to 52.3%, I2 = 99.0%) and 44.6% (95% CI, 36.1% to 53.1%, I2 = 99.0%) extracted from data from 17 cross-sectional studies (n = 11 727), 1 cohort study (n = 4804), and 1 RCT study (n = 482) from 12 countries. The prevalence of stress and depression was higher in 2020, while the prevalence of insomnia and anxiety was higher in 2021. The prevalence of mental health problems among physicians was higher than that of other frontline HCWs. The prevalence of mental health problems among frontline HCWs is higher in South America and lower in North America. Conclusions: This systematic review and meta-analysis showed that the COVID-19 epidemic have significant effects on mental health among frontline HCWs. The overall prevalence of insomnia, stress, anxiety and depression among frontline HCWs is high.